Comparative immunohistochemical study of acquired cholesteatoma in children and adults - Mohammed Bassiouny (The Egyptian Journal of Otolaryngology, 2018)
Abstract Objective To compare the histopathological structure and immunohistochemical characteristics of acquired cholesteatoma in children and adults. Patients and Methods This study was carried out on 40 patients presenting with cholesteatomatous middle-ear disease. Twenty patients were of a pediatric age group (<18 years) and the rest were adults (>18 years). Patients were admitted to the ENT Department of Alexandria University Hospital. All cholesteatoma specimens were collected intraoperatively and preserved for histopathological examination and immunohistochemical technique using the epidermal growth factor (EGF) monoclonal antibody. Results Histopathological examination of the submitted specimens showed that strips of stratified squamous epithelium with the underlying tissues were fibrous in adults, whereas cellular inflammatory infiltrates were observed in children. The degree of fibrosis was significantly higher in the adult group, whereas the pediatric group had higher inflammatory infiltrate. Immunohistochemical examination indicated significantly higher expression of EGF in children compared with adults both in the matrix and in the perimatrix of acquired cholesteatoma. Conclusion Children with acquired cholesteatoma had higher inflammatory infiltration and significant expression of EGF in both the matrix and the perimatrix with less fibrosis compared with adults, explaining the possible pathogenesis of aggressive behavior of cholesteatoma in children.